A chair for my mother - Williams, Vera B. (New York Greenwillow Books, 1982)
A child, her waitress mother, and her grandmother save dimes to buy a comfortable armchair after all their furniture is lost in a fire.
"Ages 3-8."
Keywords: Family life -- Fiction; Saving and investment -- Fiction; Chairs -- Fiction